Trends in DNA barcoding and metabarcoding - Adamowicz, Sarah J. (2019)
This open-access special issue features 12 full articles representing emerging trends from the international DNAbarcoding community. Several articles highlight how DNA-based techniques are elucidating the species diversity,biogeography, and conservation status of Africas biodiversity. Another prominent theme is the movementtowards big biodiversity data using high-throughput, individual-based DNA barcoding methods, which preservevoucher specimens and abundance data, as well as bulk sample-based metabarcoding. Methodological developments are enhancing the detection of specific species and whole communities using environmental DNA(eDNA) barcoding and metabarcoding. Data are also expanding in terms of genetic coverage; in this issue, a newdatabase is established for a secondary fungalDNAbarcode marker, and multi-kingdom, multi-marker biodiversitysurveys are gaining traction. DNA barcode sequence data, often combined with complementary markers or taxonomic information, are increasingly contributing to large-scale phylogenetic projects, with implications for understanding evolutionary history, community structure, and conservation priorities.